Upaya Penegakan Hukum Lingkungan dalam Penanganan Pencemaran Sungai Ciliwung akibat Aktivitas Mall Seasons City - Lizy Marchelina Butarbutar; Nur Wulan Ramadhani (Jurnal Hukum dan Sosial Politik, 2026)
The pollution of the Ciliwung River caused by urban and commercial activities has become an increasingly critical environmental issue, reflecting the weak effectiveness of environmental law enforcement in urban areas. This condition is evident in the area surrounding Seasons City Mall, where ecological pressure resulting from domestic waste and commercial activities has contributed to the deterioration of river water quality. This study aims to analyze the implementation of environmental law enforcement, identify the obstacles to controlling pollution in the Ciliwung River, and formulate strategies for optimizing sustainable environmental protection. The research employs a qualitative approach using normative juridical and empirical methods through observation, interviews, documentation, and literature review. The findings reveal that environmental law enforcement has been implemented through administrative supervision and waste control mechanisms; however, its effectiveness remains limited due to weak inter-agency coordination, inadequate monitoring capacity, low compliance among business actors, and limited public participation. This study concludes that strengthening integrated supervision, enforcing consistent legal sanctions, and enhancing collaboration among government institutions, business sectors, and communities are essential to achieving sustainable pollution control and environmental protection of the Ciliwung River.